Accounting for the foreground contribution to the dust emission towards Kepler's supernova remnant - Gomez, H. L. (2009)
Whether or not supernovae contribute significantly to the overall dust budget is a controversial subject. Submillimetre (sub-mm) observations, sensitive to cold dust, have shown an excess at 450 and 850 µm in young remnants Cassiopeia A (Cas A) and Kepler. Some of the submm emission from Cas A has been shown to be contaminated by unrelated material along the line of sight. In this paper, we explore the emission from material towards Kepler using sub-mm continuum imaging and spectroscopic observations of atomic and molecular gas, via H I,12CO(J = 2–1) and 13CO(J = 2–1). We detect weak CO emission (peak T ∗A = 0.2–1 K, 1–2 km s−1 full width at half-maximum) from diffuse, optically thin gas at the locations of some of the sub-mm clumps. The contribution to the sub-mm emission from foreground molecular and atomic clouds is negligible. The revised dust mass for Kepler’s remnant is 0.1–1.2 M⊙, about half of the quoted values in the original study by Morgan et al., but still sufficient to explain the origin of dust at high redshifts.